Multimodalidade em cenas de atenção conjunta: contribuições para o processo de aquisição da linguagem de uma criança surda - Silva, Paula Michely Soares da (2018)
The aim of this research is to understand the relationship between gestual and vocal productions in the scenes of joint attention of a deaf child with a cochlear implant, based on the multimodal language proposal, in which gesture and speech will compose the same cognitive and significant matrix (McNEILL, 2000). We take as a theoretical apparatus for this research considerations regarding gestures, vocal productions and joint attention as we found in the studies of Scarpa (2004, 2009), Cavalcante (1994), Cavalcante e Brandão (2012), Galhano-Rodrigues (2003, 2007, 2012), Goldin-Meadow (2003, 2013, 2014), Brandão (2010), Fonte (2011), Soares (2014), Tomasello (2003), e Costa Filho (2011, 2016). With regard to multimodality we take as a theoretical apparatus McNeill (1985, 2000), Kendon (1980, 1982, 1990), Cavalcante (2009, 2010, 2015), Ávila Nóbrega (2010), Soares (2014). In our analyzes we present a case study in three blocks, with data from a deaf child without hearing aid, hearing aid and cochlear implant. The age range of the analyzed sections corresponds to the period from six to thirty - six months, filmed in naturalistic situations of interaction with their mother. The data were transcribed in the ELAN Software, which makes it possible to present in a timely manner the occurrence and importance of the multimodal elements in the process of language acquisition. We sought to present how the presence of gestures allied to vocal production and joint attention play a significant role in acquiring the language of the deaf child. The data analysis was performed quantitatively and qualitatively point out the importance of understanding and considering the interplay between gesture and vocal productions in scenes of joint attention during the process of children's language acquisition. In addition, the data highlight joint attention as an important strategy developed by the mother to establish interaction with the deaf child. As for the gestures, the results point to the recurrence of gesture of pointing and to the growth of pantomime, especially in the third block. The children's vocal productions, on the other hand, demonstrate the appearance of babbling in all the blocks and that there is no stretch until the thirty-six months with the construction of blocks of statements. Thus, highlighting the relevance of multimodal components in the acquisition period of language allows us to think and contribute so that the dimensioning given only to perception and sound production does not leave aside the child's input process in the plane of interlocution between gestuo-vocal productions with occurrences of joint attention.